Out‐of‐State Childbirths Disproportionately Increased Among Racial and Ethnic Minorities Since the Implementation of the Tennessee Fetal Assault Law. (20th August 2020) - Choi, S.; Leslie, D.
Abstract : Research Objective: The Tennessee Fetal Assault Law (TFAL), which allowed for the prosecution of women who used narcotic drugs during pregnancy, was enacted in 2014 to reduce the incidence of neonatal abstinence syndrome in Tennessee (TN). We analyzed the association of the law's implementation with out‐of‐state childbirths among racial and ethnic minorities in TN. Study Design: Using the National Vital Statistics System's Natality Data from January 2009 to June 2016, we used multivariate logistic regression models to evaluate the probability of having out‐of‐state versus in‐state childbirths among Medicaid beneficiaries from TN compared to beneficiaries from bordering states. We employed a difference‐in‐differences approach, exploiting the change in law implementation over time (first difference) in Tennessee relative to neighboring states (second difference) and tested whether racial and ethnic minorities in TN were disproportionately affected by the TFAL. Population Studied: Our sample included all live hospital‐born singleton infants of Medicaid beneficiaries aged 18‐44 years in TN and its bordering states including Alabama, Arkansas, Georgia, Kentucky, Mississippi, Missouri, North Carolina, and Virginia. Principal Findings: We identified 1 655 256 eligible births in our study, with 284 620 born in TN and the remaining 1 370 636 born in TN's bordering states from January 2009 to June 2016. Empirical analyses showed that implementation of the TFAL was significantly associated with higher rates of out‐of‐state childbirths among TN residents and the association was higher among racial and ethnic minorities. Since the TFAL implementation, the odds of delivering out‐of‐state among non‐Hispanic whites increased by 2.5 times (OR: 2.52; 95% CI: 1.34, 4.74). During the same period, however, the odds of delivering out‐of‐state among Hispanics and African Americans increased by 3.4 times (OR: 3.36; 95% CI: 1.35, 8.37) and 7 times (OR: 7.03; 95% CI: 3.02, 16.33), respectively. Conclusions: Our findings suggest that prosecution of narcotic drug use during pregnancy can discourage in‐state delivery among Medicaid beneficiaries, and racial/ethnic minorities are more likely to deliver out‐of‐state compared with non‐Hispanic whites. Implications for Policy or Practice: Although the TFAL was discontinued in 2016, the number of states with punitive policies for drug use during pregnancy has increased from one in 1974 to 23 in 2020. Despite good intentions, the results of this study suggest that fetal assault laws may have the unintended consequence of increasing risk to both the mother and the fetus by deterring pregnant women among racial/ethnic minorities who use illicit drugs from giving birth in‐state.